Cultura organizacional y su relación con la calidad de servicio de la clínica ECOMEDIC en Quito y Guayaquil - Pincay Ganchozo, María Guadalupe (2024)
The purpose of this study was to determine the relationship between organizational culture and quality of service at the EcoMedic clinic in Guayaquil and Quito. As a methodology, field research, bibliographic and descriptive, as well as Pearson's inductive, deductive and correlation methods, were applied with the survey technique. This work was proposed in three phases, which began with a diagnosis of the current situation of both variables, through a compilation of information, where elements of the organizational culture were identified, such as communication, values and objectives, results orientation, excellence, and organizational climate. The SERVQUAL model was used to assess the quality of service. It should be noted that with these indicators, the 9 employees and 235 clients of the clinic were evaluated, giving way to the execution of the second stage, in which the relationship of the variables was determined through the application of the SPSS statistical program, which It showed a value of 0.858, which was positive according to its interpretation. Additionally, the results of the evaluation placed the organizational culture at a level of 94% and the quality of service at 91%, data that shows that the variables are at a favorable point, but it is necessary to strengthen them, which is why the third phase was used, which consisted of proposing an improvement plan with the 5W+1H matrix, which served to counteract certain shortcomings detected in the research. In conclusion, EcoMedic maintains good management at the clinic, however, it is feasible to optimize some elements of the organizational culture that allow the excellence of the service.